Protection of Expressions of Folklore in Nigeria: The Expediency of Legal Improvements - Olorunnipa , Temitope Abigail; Odunaike, Dorcas A.; Sodipo, Bankole (ABUAD Law Journal, 2025)
Rights of traditional communities to their expressions of folklore deserve to be effectively protectedthrough every legal means possible. Customary law governed expressions of folklore in the traditional sense but same is inadequate to ward-off intruders especially in the contemporary sense due to civilisation. Existing legal framework for protection through the intellectual property law systems seems inadequate. Review of these rights by the international community has indicated desire for more adequate protection in some jurisdictions. Hence, the move for sui generis measures and system to forestall abuse, misuse and misappropriation of folklore. Recent amendment of the copyright legislation of Nigeria did not cover the aspect of expressions of folklore. With the use of doctrinal method of research and an inductive content analysisof primary and secondary sources of information, this paper examines the legal regime of protection offolklore under contemporary intellectual property rights as provided under the Nigerian law with the aim of pinpointing the adequacy or otherwise of the protection so granted. The article discovers that being a multi-ethnic country and having transnational ethnic group, it is best that permission to make use of expressions of folklore resides in traditional communities where they are ascertainable than in the Nigerian Copyright Commission (NCC)where the source is uncertain or resides in more than one community and also recommends that the NCC rise to the task of performance of duties as the traditional custodians would have done.